Integrating spatial and development planning for holistic development in Batu City, Indonesia - Satti Wagistina; Ike Astuti State; Bramantiyo Kurniawan Dwi Putra; Rina Syafitri (Town and Regional Planning)
Tourism development in Batu City, Indonesia, has deviated from its official tourism master plan, highlighting the need for integrated regional planning as a critical component of successful development. A primary challenge lies in the capacity of stakeholders to implement development following established plans. This article aims to analyse the integration between spatial planning and development programme planning, focusing on cases of land-use inconsistencies such as the construction of the Jambuluwuk Resort on land designated for forestry, agriculture, and ecotourism under the 2010-2030 Batu City Spatial Plan. Data was collected through surveys involving stakeholders responsible for programme planning. The analysis employed descriptive spatial techniques alongside the SWOT-AHP (Analytical Hierarchy Process) method. The findings revealed that spatial planning served as a guiding framework for development planning, with programme alignment between spatial and development documents reaching 95.60%. However, infrastructure development planning did not fully optimise spatial planning regulations, as programme decisions were primarily driven by community needs and evolving development priorities. The study provides actionable recommendations for enhancing stakeholder engagement and planning synchronisation to support sustainable development in Batu City.